Developing Local Wisdom–Based Interactive History E-Books to Enhance Students’ Cultural Understanding: A 4D Model Approach in Kerinci Regency - Apdelmi Apdelmi; Muhammad Ihsan Dacholfany; Yunan Surono; Nurpeni Nurpeni; Heri Susanto; Said Almaududi; Firza Firza; Arif Rahim; Heni Pratiwi; Zuhri Saputra Hutabarat (Dinasti Publisher, 2026)
Globalization opens wider access to information and knowledge, enabling individuals and communities to learn and develop in new ways. The purpose of this study is to describe, develop, and test the effectiveness of interactive teaching materials based on Kenduri Sko Local Wisdom to improve students' cultural understanding. This research method uses research and development. Research and development (R&D) in the field of education is defined as a development model that adapts industrial product development. Data collection techniques used are observation, questionnaires, and written tests. The results of the study show: 1) Effective and efficient teaching materials were obtained, 2) Teaching materials based on local wisdom are effective in improving students' cultural understanding, and 3) The effectiveness of teaching materials based on local wisdom was tested to improve students' cultural understanding, 4) These results indicate that there are significant differences in students' understanding of local wisdom between using interactive history teaching materials based on local wisdom and using books available at school. The implication of using local wisdom-based history teaching materials is that it provides more meaningful learning opportunities, where they can understand history through traditions that are close to their daily lives, such as Kenduri Sko.